Eco-socialism will be anti-eugenic or it will be nothing: Towards equal exchange and the end of population. (May 2023) - Tilley, Lisa; Ajl, Max
In this article, we draw attention to similarities and synergies between eco-fascist and liberal forms of populationism which encourage reproductive injustices against Indigenous women and women of colour globally, increasingly in the name of climate change mitigation. Calls to intervene in the bodily and social autonomy of racialised women, at best, distract from ecological crisis and, at worst, encourage violent forms of reproductive injustice. We urge instead for an honest reckoning with the root problem of ecologically unequal exchange (EUE) as the system of global extraction, which enacts environmental harm and reproductive injustice. Finally, we call for an anti-imperialist eco-socialist move towards equal exchange on a world scale to end the flow of undervalued resources from the South and to limit the contaminating activities these enable. We also stress that an anti-imperialist eco-socialism needs to be attuned to the teachings of reproductive justice movements and resistant to creeping liberal eugenicism, as much as to the overt eco-fascism which has proved so deadly in recent years.